Transcriptome and functional analyses reveal ERF053 from Medicago falcata as key regulator in drought resistances - Li, Qian; Jiang, Wenbo; Jiang, Zhihu; Du, Wenxuan; Song, Jiaxing; Qiang, Zhiquan; Zhang, Bo; Pang, Yongzhen; Wang, Yuxiang (Frontiers in Plant Science, 2022)
Medicago falcata L. is an important legume forage grass with strong drought resistant, which could be utilized as an important gene pool in molecular breed of forage grass. In this study, M. falcata seedlings were treated with 400 mM mannitol to simulate drought stress, and the morphological and physiological changes were investigated, as well as the transcriptome changes of M. falcata seedlings at different treatment time points (0 h, 2 h, 6 h, 12 h, 24 h, 36 h and 48 h). Transcriptome analyses revealed four modules were closely related with drought response in M. falcata by WGCNA analysis, and four ERF transcription factor genes related with drought stress were identified (MfERF053, MfERF9, MfERF034 and MfRAP2.1). Among them, MfERF053 was highly expressed in roots, and MfERF053 protein showed transcriptional activation activity by transient expression in tobacco leaves. Overexpression of MfERF053 in Arabidopsis improved root growth, number of lateral roots and fresh weight under drought, salt stress and exogenous ABA treatments. Transgenic Arabidopsis over-expressing MfERF053 gene grew significantly better than the wild type under both drought stress and salt stress when grown in soil. Taken together, our strategy with transcriptome combined WGCNA analyses identified key transcription factor genes from M. falcata, and the selected MfERF053 gene was verified to be able to enhance drought and salt resistance when over-expressed in Arabidopsis.